Cover Image. (4th February 2022) - Zhou, Mi; Hu, Yiting; Huang, Ruoyan; Zhou, Yang; Xie, Xiaoyan; Zhang, Shidi; Jia, Shaodi; Zhang, Yunmiao; Xue, Ting; Dong, Fang; Lu, Xiaoqi; Yuan, Kai; et al.
Abstract : The cover image is based on the Original Article Right arcuate fasciculus and left uncinate fasciculus abnormalities in young smoker by Mi Zhou et al., https://doi.org/10.1111/adb.13132 .